Pengembangan Media Audio Visual Berbasis Powtoon Pada Tema 5 Ekosistem Kelas V SD - Mutiara Pulungan; Nurjannah Nurjannah (Journal Innovation In Education, 2024)
The objective of this research was to develop Powtoon-based audio-visual media on theme 5 "Ecosystem" in grade V elementary school. and to find out the feasibility of Powtoon-based audio-visual media on theme 5 "Ecosystem" in grade V elementary school. The research phase uses the ADDIE model, namely: analysis, design, development, implementation and evaluation. The analysis in this research used qualitative and quantitative analysis. The instruments used in this research were observation, documentation and questionnaires of material experts, media experts, individual and small group trials. Data from observations and documentation are analyzed descriptively qualitatively, while the data obtained from questionnaires are analyzed descriptively quantitatively by the subjects of this research, namely media expert validators, material experts and learning experts who will assess the audio-visual media developed. The object in this research, namely Powtoon-based audio-visual media on theme 3 "Ecosystem" was developed. The results of research and development of powtoon media have been declared suitable for use by grade V elementary school students in mastering the material in theme 5 of the ecosystem and the average score obtained by material validation is 91% with "very good" criteria, media validation is 94% with "very good" criteria, and the average result of teacher response is 82% with "good" criteria or can be tied properly. It can be concluded that, audio-visual media is feasible and acceptable as one of the thematic learning media in grade V elementary school.